Love and violence in Sierra Leone : mediating intimacy after conflict - Schneider, Luisa T. (Luisa Theresia), 1991- (Cambridgef ; New York, NY : Cambridge University Press, 2025)
In the decades following the civil war that took place in Sierra Leone between 1991 and 2002, new laws were passed to rebuild the state, and to prevent rape, teenage pregnancy and domestic violence. In this ethnography, Luisa T. Schneider explores the intricate semantic, empirical and socio-legal dynamics of love and violence in post-conflict Sierra Leone, challenging the oversimplification of these phenomena. Schneider underscores the limitations of imposing singular interpretations on love and violence, advocating for a nuanced, phenomenological approach that reveals how state and institutional attempts to regulate violence and loving relationships without considering local lived experience and meaning-making can yield negative consequences. By analysing how love and violence are historically constituted, experienced, and (re)produced across personal, social, legal, and political levels, this book critiques the construction of violence within gendered sexual relationships by development agencies, law makers and politicians, urging them to engage with local knowledge and experience. This title is also available as Open Access on Cambridge Core.
Access, methodology and ethics -- The impact of violence on relationships -- Loving and living relationships in Freetown today -- The spectrum of violence in relationships -- The language of violence -- Household and community mediations of violence -- Invoking the state : when adults report violence in their relationships to the police -- Minors before the law : building futures, policing sex -- Perpetrators? The consequence of the Sexual Offences Act for young men.
Title from publisher's bibliographic system (viewed on 28 Jan 2025).
Keywords: Intimate partner violence -- Sierra Leone; Sexual assault -- Law and legislation -- Sierra Leone; Sierra Leone -- Social conditions -- 1961-